Architectural design and psychological comfort of the population under Covid pandemic-19 - Khelifa, Naama; Bouzaher, Soumia; Boukhabla, Moufida (Journal of Architecture and environment of child, 2022)
On 11 March 2020, the official declaration by the World Health Organization (WHO) declared that the new corona virus is a global epidemic, and that mandatory physical separation and home isolation of patients is the primary solution for preventing disease and infection, our objective in this paper is to look for new foundations and standards for architectural design, Which produces healthy quality spaces that help residents to stay in their homes for a long time without being psychologically affected, and thus achieve psychological comfort for them inside their homes. We have followed a descriptive and analytical approach to the emerging and basic variables that help in the research, and we have used a questionnaire covering a sample of affected families that were identified with the help of statistics registered with the health services of the municipality of Sidi Okba, one of the largest municipalities in the south-east of Biskra (Algeria), and it is among its municipalities most affected by the epidemic. and in a period from the beginning of the pandemic (March 2020) until this moment (August 2021), and after collecting and analyzing the results, we extracted some new standards for architectural design that will help achieve psychological comfort for the residents inside their homes in light of the Covid 19 pandemic.